2x2+2x-1=
4+2(-3)-1=
4+(-6)-1=
4+(-7)=
-3
(x + y)^2 = (x^2 - 2xy + y^2)
First distribute the ^2 on the left side of the equation to each term inside the parenthesis:
x^2+ 2xy + y^2
Now pick one of the variables to solve for and isolate it:
(solving for x)
x^2 + 2xy + y^2 = x^2 - 2xy + y^2
x^2+ 2xy = x^2 - 2xy
2xy = -2xy
-x = x
x = 0
When you solve for y in the equation it will turn out to be 0 as well
Answer:
the answer is b I know this because I'm a very young person but I'm a very young man who has been a great person for the last two decades so I'm not really into this
Step-by-step explanation:
I just don't want you back in here and you know this because I know this because you are a good friend of yours but you have no reason for me not knowing that I was in love and you are a great man but you have no idea how to do this 6AM 6AM I know this because you have to be with him to be a great person to be able and be able and be happy and you will have a great time
PERIOD BOO
Answer:
Hey
Definition:-
A square root is a number which produces a specific quantity when multiplied by itself.
Example:-
Suppose the area of a square of side 6 cm is given by 6 × 6 = 36 cm².
Therefore 36 is said to be the square of 6. We write 6² = 36 and we read the ‘the square root of 6 is 36' or simply ‘6 squared is 36.'
hope this helps
Answer:
8i + 4
Step-by-step explanation:
Add/subtract like terms:
7 - 3
= 4
-4i - (-12i)
-4i + 12i
= 8i
Add these together:
8i + 4
So, the simplified expression is 8i + 4